Improving the electrical properties of poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] by doping with camphor sulfonic acid for energy storage applications - Uludag, Cem; Karabul, Yasar; Kilic, Mehmet; Koc, Kenan; Alveroglu, Esra; Ozdemir, Zeynep Guven (WILEY, 2022)
This study examines a wide range of spectroscopic, structural and electrical properties of poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV)/camphor sulfonic acid (CSA) composites. Incorporation of CSA into the polymer matrix is confirmed by FTIR, UV, PL, scanning electron microscope, and atomic force microscopy results, also DC conductivity analysis shows that it affects the electric nature of the polymer differently from linear change. On the other hand, when the frequency-dependent electrical properties are evaluated, it is seen that MEH-PPV composite with the highest CSA contribution stands out for energy storage applications compared to pure MEH-PPV with increased epsilon '$$ {\varepsilon} {\prime } $$ and reduced epsilon ''$$ {\varepsilon} {\prime \prime } $$ values. Moreover, the electrical modulus analysis showes that the increased CSA contribution contributed to the long-range mobility of the charge carriers. Furthermore, Cole-Cole curves are drawn in the complex electric modulus plane both confirm a non-Debye type relaxation and support the existence of Maxwell-Wagner type polarization in the samples.
Keywords: composites; conducting polymers; dielectric properties; the pristine and CSA doped MEH-PPV; MEH-PPV; DIELECTRIC-PROPERTIES; POLYANILINE; RELAXATION; DIFFUSION; Polymer Science